2021
DOI: 10.1002/ejoc.202100894
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acids as Versatile Tools for Organocatalytic Asymmetric Transfer Hydrogenations

Abstract: Herein, recent developments in the field of organocatalytic asymmetric transfer hydrogenation (ATH) of C=N, C=O and C=C double bonds using chiral phosphoric acid catalysis are reviewed. This still rapidly growing area of asymmetric catalysis relies on metal-free catalysts in combination with biomimetic hydrogen sources. Chiral phosphoric acids have proven to be extremely versatile tools in this area, providing highly active and enantioselective alternatives for the asymmetric reduction of α,β-unsaturated carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 112 publications
(122 reference statements)
0
13
0
Order By: Relevance
“…During the last decade, CPAs have inspired the synthesis of new and more acidic organocatalysts such as disulfonimides, N -triflylphosphoramides or imidodiphosphorimidates. 3–8 However, the interest in the applications of CPAs in chemistry is still growing and, up to date, they have proved to be highly efficient catalysts for several enantioselective transformations such as S N 1, 9 transfer hydrogenation, 10–13 dearomatization 14 or cycloadition 15 reactions among others. 16–20 Moreover, they have also gained attention in kinetic resolution and deracemization processes, 21 as chiral ligands for metal-catalysed reactions 22,23 or metal-CPA co-catalysis, 24–27 and have promising perspectives as chiral inductors in photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, CPAs have inspired the synthesis of new and more acidic organocatalysts such as disulfonimides, N -triflylphosphoramides or imidodiphosphorimidates. 3–8 However, the interest in the applications of CPAs in chemistry is still growing and, up to date, they have proved to be highly efficient catalysts for several enantioselective transformations such as S N 1, 9 transfer hydrogenation, 10–13 dearomatization 14 or cycloadition 15 reactions among others. 16–20 Moreover, they have also gained attention in kinetic resolution and deracemization processes, 21 as chiral ligands for metal-catalysed reactions 22,23 or metal-CPA co-catalysis, 24–27 and have promising perspectives as chiral inductors in photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoric acids based on chiral BINOL, H 8 -BINOL, or SPINOL 14,15 backbones proved to be useful in the formation of all-carbon quaternary stereocenters, [16][17][18][19] chiral axes, [20][21][22] and compounds with planar chirality. 23 A few applications of CPAs include asymmetric transfer hydrogenations, 24 dynamic kinetic resolutions and desymmetrization, 25,26 cycloaddition and annulation reactions, 27 and S N 1 substitutions, 28,29 and they have emerged as promising molecules in photoredox transformations. [30][31][32][33][34][35] CPAs are versatile organocatalysts with increasing applications in academia and industry.…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of phopshothionates is that they contain a stable acidic P -stereogenic center, and in this regard these compounds can be considered as chiral Brønsted acids. P -contatining Brønsted acids found wide-spread application as organocatalysts, and BINOL-based C 2 -symmetric derivatives are benchmark catalysts [ 36 , 37 ]. A few studies suggested that C 1 -symmetric phopshothionates can also be used as organocatalysts, but in those instances, the catalyst scaffold contained other functional groups besides the P(S)OH moiety, and it was postulated that this combined activation is responsible for the asymmetric induction [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%